Biodiversity and Seasonal Fluctuations of Zooplanktons in Jagatunga Samudra Reservoir of Kandhar, India - C. A. Jawale2, B. J. Ugale1*, (Journal of Experimental Sciences, 2010)
The zooplankton community is a heterogeneous assemblage of animals covering many taxonomic groups comprising mostly of invertebrates. It includes herbivores, carnivores, detritivores and omnivores constituting an efficient food chain utilizing the energy transfer from the primary to the secondary level. Thus zooplankton forms a major link in the food chain and is significant in assessing the fertility of the water bodies. The study of zooplankton communities is important because it provides way of predicting and increasing the productivity of lakes. The present paper deals with the biodiversity and seasonal fluctuations of zooplanktons of Jagatunga Samudra Reservoir, Kandhar, Dist. Nanded, (M.S), India. The maximum number of zooplankton observed during winter season and minimum during monsoon season. ———————————————————————————– 1S. K. M. Gunjoti, Tq. Omerga, Dist. Osmanabad. (M.S.) 413613, India; 2S. M. P. College Murum Tq. Omerga, Dist. Osmanabad. (M.S.), India * Corresponding Author, Email: bju_skmg@rediffmail.com Please Cite This Article As: B. J. Ugale, C. A. Jawale. 2010. Biodiversity and Seasonal Fluctuations of Zooplanktons in Jagatunga Samudra Reservoir of Kandhar, India. J. Exp. Sci. 1(2): 01-02.